Comprehensive Review of Technological Integration in Nursing Workflows: Balancing Innovation and Patient-Centered Care - Alnasser, Almuhannad Saleh; Alenazi, Nurah Onazan Mahal; Almnahy, Sulaiman Ibrahem Abdulziz; Alnasser, Almuayyadsa Saleh Ali; Balobaid, Abeer Mubarak; Al mautairi, Abdulaziz fahad masha; Alharbi, Athei Obed N; Alwadaeen, Fahad Abdullah Fahad; Alenzi, Anwar Onayzan Mahal; Al-Harbi, Sulaiman Ali (Journal of Ecohumanism, 2024)
The advanced application of technology in nursing has greatly impacted the present healthcare delivery process by improving the efficacy, precision, and safety of nursing. Technological advancements, including EHRs, telehealth, AI, and robotic systems, have caused shifts in the usual functions of nurses. However, these technologies have unique considerations that must be balanced with patients’ needs and values. This review is intended to raise and discuss questions regarding the development and use of technologies in the nursing practice environment, their benefits and drawbacks, and the conflict between the enhancement of technology adoption and the fundamental values of the nursing profession. This review of the current literature, as well as several empirical works and some cases, reveals the benefits and the challenges for nursing professionals regarding the use of technologies. This review also provides suggestions for improving how technology is implemented into nursing processes to develop effectiveness in a functional organization and improve patient care quality.